Pengaruh Promosi, Program dan Kemudahan Investasi Emas Berbasis Mobile Banking terhadap Peningkatan Laba Bank Syariah Indonesia - Yuwanda, Subhan Arief; Zulkarnnaeni, Achmad Syahfrudin; Aspirandi, Rendy Mirwan (Universitas Negeri Padang, 2025)
The aim of the research is to test the effect of promotions, programs and ease of investing in gold, by utilizing technology mobile banking towards increasing profits at the Indonesian sharia bank KCP Lumajang. This research method uses a quantitative approach. The research sample consisted of 40 employees of Bank Syariah Indonesia KCP Lumajang, using techniques Probability Sampling using method saturated sampling. Analysis of research data using Multiple Regression Analysis and Moderated Regression Analysis (MRA) with software SPSS 25. The research results show that gold investment promotion, gold investment programs, and ease of gold investment have a significant effect on increasing profits at Bank Syariah Indonesia KCP Lumajang. Apart from that, the use of technology mobile banking Act as a director, which strengthens the influence of these three variables on increasing profits. This indicates that digitalization of sharia banking services can increase the effectiveness of gold investment strategies, thereby having a positive impact on bank profitability. Optimization mobile banking, increasing financial literacy, and data-based marketing strategies can increase customer loyalty. Further research, the role of fintech and blockchain technology in Islamic bank gold investment.